2014
DOI: 10.1088/0031-8949/89/04/045103
|View full text |Cite
|
Sign up to set email alerts
|

AnSU(2)⊗SU(2) Jaynes–Cummings model with a maximum energy level

Abstract: The SU(2)⊗SU(2) extension of the Jaynes–Cummings model provides a quantum mechanical system with a finite Hilbert space together with a maximum energy level in the spectrum. The model, which remains exactly solvable, is based on the replacement of the bosonic (creation and annihilation) operators by spin operators defined to act within a definite SU(2) irreducible representation, in such a way that the photon field has a finite number of excitations. The usual Heisenberg–Weyl () algebra can be obtained by cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Let us keep k finite and investigate the physical properties of the extended Dicke model (9). It is worth underlying that in a foregoing investigation we introduced the k-extended Jaynes-Cumming model (in the dipole and rotating wave approximations), which remains exactly solvable with the new SU(2) ⊗ SU(2) dynamical algebra [16]. There we showed that the temporal evolution of both the atomic and field quantum properties (e.g.…”
Section: The K-dicke Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…Let us keep k finite and investigate the physical properties of the extended Dicke model (9). It is worth underlying that in a foregoing investigation we introduced the k-extended Jaynes-Cumming model (in the dipole and rotating wave approximations), which remains exactly solvable with the new SU(2) ⊗ SU(2) dynamical algebra [16]. There we showed that the temporal evolution of both the atomic and field quantum properties (e.g.…”
Section: The K-dicke Modelmentioning
confidence: 96%
“…for the photon sector, which contracts to the Heisenberg-Weyl coherent state |α in the large k-representation limit [16,29]. Here, η = tan(ψ/2)e iϕ , ψ ∈ [0, π) and ϕ ∈ [0, 2π).…”
Section: Mean Field Analysismentioning
confidence: 99%
“…The JCM depicts a two-level quantum system (a spin or a qubit) interacting with a single bosonic mode of radiation. Despite its solvability [2,4,9], the model remains realistic enough to stimulate research in diverse fields, encompassing applied group theory [9][10][11], investigations related to quantum integrability [12,13], and extending to quantum information processing [14][15][16]. This text further explores a specific application of the Jaynes-Cummings model for detecting non-orthogonal quantum states, as proposed in Ref.…”
Section: Introductionmentioning
confidence: 99%